Echocardiographic assessment of the impact of cardiovascular risk factors on left ventricular systolic function in patients with acute myocardial infarction - Verma, Vijay Kumar; Rawat, Ramakant; Sagar, Vidya; Kumar, Granth (International Journal of Research in Medical Sciences, 2017)
Background: Objectives of current study were to determine the magnitude of left ventricular systolic dysfunction in patients with acute myocardial infarction in the rural sub-population of Uttar Pradesh in India and to evaluate the impact of cardiovascular risk factors on the risk of impairment of left ventricular systolic function. Methods: One hundred and fifty seven consecutive patients with first acute myocardial infarction were enrolled into the study. Most patients were male (73.2%) and the mean age of presentation was 52.7 years. Two dimensional echocardiography was utilized to assess conventional parameters such as Left Ventricular End-Diastolic Diameter (LVEDD), Left Ventricular End-Systolic Diameter (LVESD), LV End-Diastolic Volume (LVEDV), LV End-Systolic Volume (LVESV) and Left Ventricular Ejection Fraction (LVEF). The LV volumes (end-systolic and end-diastolic) and LVEF were calculated from the conventional apical two-and four-chamber images using the biplane Simpson’s technique. LV systolic function was considered depressed when LVEF was less than 45%. The chi-square test was used in the statistical analysis to compare proportions and a logistic regression model was used to assess the independent effect of the each variable. Results:The study projects a high proportion (42.7% of the patient population) of left ventricular systolic dysfunction in patients with Acute Myocardial Infarction (AMI). No association was found between gender or age and LV systolic dysfunction. The proportion of patients with diabetes mellitus was higher in the sub-group of patients with impaired LV systolic function (45.2% vs. 30.2%, P = 0.01); the proportion of patients with history of current or past smoking was also higher in the sub-group of patients with impaired LV systolic function (48.9% vs. 34.2%, P = 0.03). On the other hand, hypertension and dyslipidemia were not associated with impaired LVEF. After adjustment of other variables, diabetes and smoking were associated with a significantly higher risk of LV systolic dysfunction (diabetes: OR = 3.73; 95% CI = 1.25-11.16; smoking: OR = 3.8; 95% CI = 1.37-11.05). Conclusion:Since the proportion of patients with LV systolic dysfunction in patients with AMI remains relatively high, LV systolic function variables such as LVEF and LVESV should be echocardiographically evaluated in all patients with AMI. Since the post-infarction LV systolic function remains the single most important determinant of survival, treatment of AMI patients should be aimed at limitation of infarct size and prevention of ventricular dilation. Moreover, cardiovascular risk factors such as diabetes mellitus and smoking have a significant impact on the likelihood of impairment of LV systolic function in patients with AMI and hence could influence long-term prognosis.